Archaeological Textiles of 2/2 Diagonal Twill Found in the Coastal Cemeteries of the 1st–12th Centuries in Lithuania - Pečeliūnaitė-Bazienė, Elvyra (Archaeologia Lituana, 2004)
We still have very little information about archaeological textiles dated to the 1st–12th c. that were found in Lithuania. For many years there were no investigations carried out in this field. There are just 2 articles that touch upon investigations of the Roman period textiles (Pečeliūnaitė, 1998; Pečeliūnaitė-Bazienė, 2002). 2/2 diagonal twill was preferred because at the moment the best-investigated textiles have this weave. The fibre was determined in laboratory of Lithuanian National museum and P. Gudynas Restoration and Conservation Centre of museum pieces. Almost 200 textile fragments found in this territory has been investigated. 2/2 diagonal twill was the most popular weave within whole period. The beginning of twill weave could be seen in the primitive basketry that was observed on the mat from Šventoji, in late Neolithic 1A settlement. There has not yet been found any textiles dated to the Bronze and Early Iron age in the whole Lithuania. So we have no proof of the fact when woven textiles of 2/2 diagonal twill weave has appeared in this territory. The first textile remains of 2/2 twill come from the Roman period from which we have just II pieces. The main feature of these textiles is that all of them have Z/S or S/Z spin direction except 1 Z/Z peace from Kurmaičiai cemetery (Kretingos district) (there was found no borders, so we can’t say exactly which thread belongs to warp or weft but they are not spin-patterned). The average of textile quality is 10/10-threads/1 cm, all are wool en and they are local made. Very few textiles come from the 5–7th centuries. There are just 6 pieces found in Reketė, Lazdininkai, Užpelkiai cemeteries. All of them are woollen and as in the Roman period are of different spin direction. The quality is about 11/10-threads/1 cm and they are also local made. Starting with the 8th century there could be observed some changes in this territory. 2/2 diagonal twill is not so strictly dominant any more. 2/2-diamond twill and 2/2 herringbone twill of Z/S and S/Z spin direction appears in greater quantity. 2/2-diagonal twill is of different spin direction and Z/Z spun as well. The first type is dominant. Compared together, Z/Z spun twill is most often 9/8; twill of different spin direction is 11/10. In the 9–12th centuries 2/2 diagonal twill gets its variations. The main part of textiles was found in Palanga, Genčai I, Kiauleikiai and Pryšmančiai cemeteries. 2/2 twill Szz/Z (or Sz/z) was found in almost all the cemeteries. One piece Szz/S (or Sz/s) was found in Genčai, grave No 44. These textiles appear about the 9th century and continue till the 12th century. Such kind of textiles were found in Finland and identified as Pappilanmaki type. The same textiles were found in Latvia and Russia (Great Nowgorod). 2/2 twill Szz/Z or Szz/S were found just in the coastal part of Lithuania, except one piece from Paluknys (Raseinių district) and one from Gintališkė (Plungės district), both of them are situated in the western part of Lithuania. Between 2/2 diagonal twill textiles this type makes 23 per cent and among all the other types of weaves it makes 11 per cent. They are of different count between 3/5 and 18/14 and the average is 8/9. In my opinion the idea of this type came from Finland but a quite big amount of 2/2 twill Szz/Z could be interpreted as a local product. Another interesting feature of these textiles is that almost all of them were found in men graves. The same situation was observed in Latvia. Latvian and our material show that these textiles could be referable to the overcoats or tunics. This feature is not the only one showing similarities that appears in the eastern part of the Baltic Sea. The other common feature is the use of bronze beads ornaments on the textiles. Some relationships in weaving tendencies could be observed in Palanga – a trade centre, where an ornamented loom-weight was found. Such weights are quite rare and similar one was found at Raisio Mulli settlement of early Middle Ages nearby Turku in Finland (Žulkus, 1997, p. 254). There were also found 14 pieces of textiles, all Z/Z of a hard – spun warp and a soft-spun weft and with uneven proportion between warp and weft. The average is 9/7 but 6/5 (Pryšmančiai, Stragnai) and 14/10 (Stragnai) was found as well. One piece of the same proportion was found in Stragnai cemetery and was of Z/S. Warp and weft in this fragment were different dyed – warp was dark-brown, and weft was light-brown coloured. Interesting material was investigated from Stragnai. One piece preserved a side-border that is tubular side-selvage. This kind of borders was common in Latvia, used with vilajne; they were found in Gdansk (Poland), Great Novgorod, Staraja Ladoga (Russia). Such kind of borders has been found in Denmark since Bronze Age. Unfortunately the material of Stragnai can’t be related with any other finds and exactly dated. But comparing all the material with other textiles from different cemeteries it can be said that these textiles belong to the 8th–12th and even to the 13th centuries. 2 pieces were found with rep sides, both Z/Z, one had 6/6, the other one 11/9 threads. All textiles except one found in Anduliai, grave No 1 are made of wool. But the latter is questionable because the archaeologist himself without any laboratory analysis gave this fact of linen textile. The fragment didn’t survive and it is impossible to review it. The weaving faults, irregularities show that the textiles of 2/2 diagonal twill were woven on the warp-weighted loom. The starting borders with tablet woven bands found on the textiles of other weaves (2/2 herringbone, lozenge twill) can sustain the same theory. A lot of loom weights were found in the settlements of the coastal Lithuania. One of the factors of horizontal loom is a big amount of 2/1 or 1/2 twills. There are found just few such kind of textiles dated to the 10th–12th c. (Palanga, Gr. 269; Kiauleikiai Gr. 17–19 (?); Stragnai). At that time more it is more observed that lozenge twill of a high quality replaces 2/2 diagonal twill. Summing up, the material shows that the situation in the coastal region of Lithuania has its own traditions. The main feature of 2/2 diagonal textiles was Z/S or S/Z spin direction that was predominant during all the periods. The same direction dominates in the textiles of other weaves (2/2 herringbone twill, 2/2 diamond twill). In comparison with the other part of Lithuania, a difference could be observed. In the 1st–12th centuries there the amount of textiles of different spin direction and Z/Z textiles was almost the same, the first one a little bit predominated. The same could be said about the other weaves. Making comparison between material of Lithuanian coastal territory and North and Central Europe, it could be stated that this material is closer to the Central Europe because of the spin direction.